An Integrated Approach for a New Pattern in Pediatric Primary Care: Interaction Mediation for Active and Efficient Medical Consultations - Ranieri, Jessica; Guerra, Federica; Cilli, Eleonora; Di Giacomo, Dina (Frontiers in Pediatrics, 2020)
Background: This study analysed the impact of an innovative integrated approach in paediatric care on children’s behaviour and cooperation during care. Methods: The participants included 75 children aged 3 to 8 years (30 girls and 45 boys) recruited from a paediatric surgery department. The sample was categorised into three groups according to experimental condition: the Control, Playing, and Interaction groups. Results: A one-way ANOVA revealed significant differences in cooperation between the three groups (F(2,1)=5.52; p=0.006). A post-hoc analysis showed better performance in the Interaction group (p=0.002) compared to the Control group during clinical care. The Control group also showed less cooperation compared to the Playing group (p=0.009). Conclusions: The findings indicate that distraction before medical care can positively influence children’s behaviour, increasing their cooperation in medical settings. Future studies could objectively analyse physiological changes in children during medical care to better relieve anxiety and provide them with more efficient care